A utilização de recursos lúdico-manipulativos nas aulas de Matemática para facilitar o aprendizado das operações com números racionais na Rede Estadual de Ensino - Freiman, Joglicia Gonoring Rodrigues (2023)
The purpose of this work is to help Mathematics teachers of the State’s Public Education System from 7th grade, elementary school, to the 1 st grade, high school. For the use of ludic resources as support and methodology in the teaching of Mathematics, specifically in operations with rational numbers. In the elective discipline, “Educational Games”, in the 2nd trimester of the Escola Estadual de Ensino Fundamental e Médio Alice Holzmeister, we have developed activities that arouse the interest of the students and seek to facilitate the learning of contents necessary for the development of the teaching of mathematics, such as, rational numbers and their operations. Among these resources we will have the memory games in which we work numerical expressions involving radicals, and powers with natural exponent, operations with integers; Rational track game, where we work on basic operations with rational numbers, recognition of decimal representations of rational numbers as an extension of the decimal numbering system identifying the existence of “orders” such as tenths, hundredths and thousandths, and recognizing the different representations of a rational number; Potentiation Roulette, in which we develop the concepts of powers of rational numbers with integer exponents; Fractions puzzle that relates equivalent fractions and their geometric representations, as well as, the improper fractions associating the geometric representation to the sum of the integer part with the fractional part and consequently to the mixed number. The material produced will be made available to the school’s mathematics teachers to assist in classes.